KARAKTERISASI BENIH DAN KEKERABATAN KULTIVAR PADI LOKAL PASANG SURUT DI KABUPATEN INDRAGIRI HILIR - nursida, nursida; Suliabsyah, Irfan; Swasty, Etty; Syarif, Auzar (Jurnal Agro Indragiri, 2024)
Similarity analysis was carried out on the characteristics of local type tidal rice grain in Indragiri Hilit Regency in January-October 2015 in Indragiri Hilir Regency. This research aims to inventory, characterize and determine the relationship between each type of local tidal rice grain in Indragiri Hilir Regency. This research uses a qualitative-quantitative description method. The beginning of this research was to explore the types of rice grains in each village and sub-district of Indfagiri Hilir Regency, then they were characterized and analyzed using the agglomerative method by calculating the distance between relatives using hierarchical cluster average linkage (between gropus). The research results show that Indragiri Hilir Regency has 27 local tidal rice cultivars. These cultivars consist of 'Karya Kuning', 'Karanduku', 'Ramos', 'Pulut Putih', 'Pandan Wangi', 'Ordinary', 'Lembu Sawah Merah', 'Karya Merah', 'Pulut Hitam', ' Pariaman', 'Lembu Sawah', 'Karya Tinggi', 'Panama', 'Batang Tuaka', 'Ir Super', 'Batang Piaman', 'Maron', 'Merah Putih', 'Serang', 'Putri Malu', 'Super', 'Opium', 'White', 'Kuatik', 'Frog', 'Lentik Bamban', 'Sere'. Morphological characters that differentiate rice cultivars are grain characteristics (length, width, thickness, weight of 100 seeds, grain surface shape, grain surface color, sterile lemma length, grain tip color, grain tip tail feather color and grain tip tail feather length), character rice (length, width, thickness, ratio of length to width, and color of rice epidermis). Phenetic analysis using the Minitab Release version 17 program divided 27 local tidal rice cultivars into 9 clusters at a similarity level of 56.78%. Which consists of group 1, consisting of Karya Kuning, Karya Merah, Maron, Pulut Putih, Putih, Putri Malu, Merah Putih, Super; Group II consists of Karanduku, Opium and Lembu Sawah Merah; cluster III consists of Ramos, Batang Tuaka, Karya Tinggi, Serang and Pariaman, cluster IV consists of paddy cattle; Group V consists of Kuatik, Serai, Lentik Bamban, Kodok, Group VI consists of Ordinary and Batang Piaman and groups VII, VIII and IX respectively consist of Pandan Wangi, Super and Pulut Hitam.